2022
DOI: 10.3390/antibiotics11081129
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Library of Escherichia coli Transporter Knockout Strains to Identify Transport Pathways of Antibiotics

Abstract: Antibiotic resistance is a major global healthcare issue. Antibiotic compounds cross the bacterial cell membrane via membrane transporters, and a major mechanism of antibiotic resistance is through modification of the membrane transporters to increase the efflux or reduce the influx of antibiotics. Targeting these transporters is a potential avenue to combat antibiotic resistance. In this study, we used an automated screening pipeline to evaluate the growth of a library of 447 Escherichia coli transporter knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Utilizing evidence that transporter manipulation affects resistance or sensitivity to toxic compounds, we screened transporter deletion libraries covering a substantial portion of annotated transporter genes (Lennen et al., 2023 ; Pereira et al., 2019 , 2020 ; Radi, SalcedoSora, et al., 2022 ). Specifically, we screened 444 E. coli and 305 S. cerevisiae individual transporter knockout strains, derived from the Keio and YKO collections, respectively (Table S4 , Figure S2a,b ) (Munro & Kell, 2022 ; Wang et al., 2021 ; Yang et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing evidence that transporter manipulation affects resistance or sensitivity to toxic compounds, we screened transporter deletion libraries covering a substantial portion of annotated transporter genes (Lennen et al., 2023 ; Pereira et al., 2019 , 2020 ; Radi, SalcedoSora, et al., 2022 ). Specifically, we screened 444 E. coli and 305 S. cerevisiae individual transporter knockout strains, derived from the Keio and YKO collections, respectively (Table S4 , Figure S2a,b ) (Munro & Kell, 2022 ; Wang et al., 2021 ; Yang et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the numerous benefits of transporter engineering, it remains underutilized in strain engineering cycles due to a lack of knowledge about transporter substrate specificities. Various strategies aside from TALE have been employed to associate substrates with their respective transporters, including toxicity‐based screening of transporter knockout or metagenomic libraries (Acton et al., 2017 ; Malla et al., 2022 ; Munro & Kell, 2022 ; Yang et al., 2022 ). More recently, genetically encoded biosensors have facilitated the discovery of new transporters for specific compounds by linking intracellular compound concentrations to detectable signals (Genee et al., 2016 ; Wang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…1). Previous studies have revealed that UhpB affects fosfomycin resistance via regulation of the expression of a hexose phosphate transporter UhpT (18, 19). The MICs of several antibiotics were also changed in the Δ phoQ mutant (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we also plotted MIC data from wild-type E. coli strains (Figure 1B). We selected different wild-type strains, such as: AG100 (Cohen et al, 1988;Okusu et al, 1996;Alekshun and Levy, 1997;Oethinger et al, 2000;Randall and Woodward, 2002;Visalli et al, 2003;Nicoloff et al, 2006;Bohnert et al, 2008;Keeney et al, 2008;Wehmeier et al, 2009;Yilmaz et al, 2015;Schuster et al, 2016;Song et al, 2016;Vergalli et al, 2020;Ferrand et al, 2023), ATCC25922 reference strain from EUCAST 2023 (Chollet et al, 2004;Aires and Nikaido, 2005;Lim Nikaido, 2010;Li et al, 2011;Sutcliffe et al, 2013;Whalen et al, 2015; Société Française de Microbiologie, 2023), JM101 (George et al, 1995), BW1556 (Munro and Kell, 2022) and BW25113 (Plé et al, 2022). Not all antibiotics have been assessed against strains overproducing AcrAB-TolC.…”
Section: Review Approachmentioning
confidence: 99%